2020
DOI: 10.1029/2019gl086761
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification Has Impacted Coral Growth on the Great Barrier Reef

Abstract: Ocean acidification (OA) reduces the concentration of seawater carbonate ions that stony corals need to produce their calcium carbonate skeletons and is considered a significant threat to the functional integrity of coral reef ecosystems. However, detection and attribution of OA impact on corals in nature are confounded by concurrent environmental changes, including ocean warming. Here we use a numerical model to isolate the effects of OA and temperature and show that OA alone has caused 13 ± 3% decline in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Besides pH cf , other calcifying fluid carbonate system parameters calculated from bulk derived δ 11 B and B/ Ca also exhibit a seawater temperature dependency, such as DIC cf (r 2 = 0.72, p < 0.01, n = 10, Figure 6c) and TA cf (r 2 = 0.63, p < 0.01, n = 10, Figure 6d). Similarly, sub-annual variations in skeletal density suggest some positive relation with temperature, with lower density values in autumn and winter when seawater temperatures are low, and higher density in spring and summer under higher seawater temperatures (Figures 3a and 3b), consistent with faster aragonite precipitation and thus skeletal densification at higher temperatures (Guo et al, 2020;Mollica et al, 2018). However, these sub-annual skeletal densities exhibited an apparent negative correlation with aragonite Ω cf (r 2 = 0.44, p = 0.04, n = 5, Figure 6e), different from the positive correlation between inter-annual skeletal density and Ω cf observed in Porites collected from several Pacific reefs in Mollica et al (2018).…”
Section: Variability In Ph Cf Upregulationmentioning
confidence: 72%
See 1 more Smart Citation
“…Besides pH cf , other calcifying fluid carbonate system parameters calculated from bulk derived δ 11 B and B/ Ca also exhibit a seawater temperature dependency, such as DIC cf (r 2 = 0.72, p < 0.01, n = 10, Figure 6c) and TA cf (r 2 = 0.63, p < 0.01, n = 10, Figure 6d). Similarly, sub-annual variations in skeletal density suggest some positive relation with temperature, with lower density values in autumn and winter when seawater temperatures are low, and higher density in spring and summer under higher seawater temperatures (Figures 3a and 3b), consistent with faster aragonite precipitation and thus skeletal densification at higher temperatures (Guo et al, 2020;Mollica et al, 2018). However, these sub-annual skeletal densities exhibited an apparent negative correlation with aragonite Ω cf (r 2 = 0.44, p = 0.04, n = 5, Figure 6e), different from the positive correlation between inter-annual skeletal density and Ω cf observed in Porites collected from several Pacific reefs in Mollica et al (2018).…”
Section: Variability In Ph Cf Upregulationmentioning
confidence: 72%
“…(2018). This difference likely reflects the interplay of multiple factors influencing coral skeletal density (e.g., extension rates, temperature, and Ω cf ) on different time scales (Guo et al., 2020). Overall, results support that at our study site coral calcification is affected by physiological modification of the calcifying fluid carbonate chemistry and that these modifications primarily follow variations in ambient seawater temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant decline in density, however, during the last seven years for P. strigosa that could not be attributed to river runoff or bleaching (Table 2). This decline in density within the past decade could be the start of a longer-term decline like that found in massive Porites on the GBR and in three different species of coral on the Florida Reef Tract, including the two studied herein (Helmle et al 2011;Rippe et al 2018;Guo et al 2020). Indeed, Hu et al (2018) showed that the rate of OA at FGB was higher than the rate in the open ocean from 2007 to 2017, which overlaps with the significant decline in skeletal density of P. strigosa (Table 2).…”
Section: Pseudodiploria Strigosamentioning
confidence: 67%
“…The impact of runoff from the Mississippi and Atchafalaya Rivers can effectively erase any OA signal because runoff impacts surface productivity, as well as directly modifies seawater chemistry, both of which introduce variability that makes a long-term OA signal difficult to detect. OA is expected to reduce coral calcification and/or cause a decline in skeletal density (Chan and Connolly 2013;Mollica et al 2018;Guo et al 2020). There were no declines in long-term calcification rates or skeletal density of the corals analyzed from FGB; calcification rates have increased in both coral species, whereas skeletal density did not exhibit any trends (Fig.…”
Section: Pseudodiploria Strigosamentioning
confidence: 93%
See 1 more Smart Citation